Biomechanical Analysis Between PEEK and Titanium Screw-rods Spinal Construct Subjected to Fatigue Loading. Issue 3 (April 2015) - Chou, Wen-Kai; Chien, Andy; Wang, Jaw-Lin
<x xml:space="preserve">Abstract</x> Study Design: An in vitro fatigue loading test with porcine specimens. Objectives: To comparatively analyze the in vitro biomechanical performance of Polyetheretherketone (PEEK) and Titanium rods construct subjected to a battery of fatigue loading testing. Summary of Background Data: PEEK rods construct has been proposed to allow better load sharing among spinal components than the more traditional Titanium rods constructs. However, such proposal has largely derived from single-load in vitro testing and the biomechanical differences when subjected to fatigue loading remain unknown. Methods: Twenty-four fresh 4-level motion segment were harvested from porcine. Specimens were randomly assigned into 3 groups: (1) intact, (2) destabilized group with Titanium alloy rods, and (3) destabilized group with PEEK rods. All specimens were subjected to a fatigue loading procedure with the disk height and intradiscal pressure (IDP) of the instrumented and adjacent levels were recorded and used for analysis. The stress levels on the rods and bone stress near the screw-bone interface were also collected to investigate the likely failure rates of the 2 constructs. Results: Titanium rods construct demonstrated a minimum amount of loss of disk height and IDP at the instrumented level; however, a significant loss of the disk height and IDP at adjacent levels compared with the intact spine were identified. In contrast, the disk height and IDP of the PEEK rods were found to be comparable with those of the intact spine for all levels. The PEEK rods group also showed significantly less bone stress near the screw-bone interface compared with the Titanium rods group. Conclusions: The current study has demonstrated the differences in biomechanical characteristics of PEEK and Titanium rods construct when subjected to fatigue loading. More specifically, the result is indicative of the potential benefits of the PEEK rods construct in reducing the risks of adjacent segment disease and implant failure rates.